ANGI-1 Impact of neoadjuvant bevacizumab on transcriptional factor for stemness, macrophage polarization, and oxygenation of tumor microenvironment in glioblastoma. (6th December 2021) - Tanaka, Toshihide; Takei, Jun; Teshigawara, Akihiko; Tohmoto, Kyoichi; Yamamoto, Yohei; Hasegawa, Yuzuru; Tamura, Ryouta; Sasaki, Hikaru; Akasaki, Yasuharu; Murayama, Yuichi
Abstract: Background: Previously we reported that bevacizumab (Bev) produces tumor oxygenation with immunosupportive tumor microenvironment (TME) and inhibition of stemness. To confirm whether those effects might contribute prolongation of clinical outcome, in the present study paired samples from same patients with newly diagnosed GBM who received Bev during its effectiveness and refractoriness were investigated by immunohistochemistry. Methods: Eighteen samples from 9 patients with newly diagnosed GBM who received preoperative neoadjuvant Bev (neoBev) followed by surgical operation and chemoradiotherapy in addition to salvage surgery after recurrence were investigated. Expressions of FOXM1, HIF-1, and CD163 were evaluated by immunohistochemistry. Overall survial (OS) were analyzed with the present cohort divided into two groups between good and poor responder (GR and PR, respectively) of Bev defined as tumor regression rate judged by T1 gadolinium enhancement (T1Gd) and fluid attenuated inversion recovery (FLAIR) images. Results: In the group of good responder of T1Gd (T1Gd-GR; defined as >38% of regression rate after neoBev), OS was prolonged compared with T1Gd-PR along with inhibition of FOXM1 expression and HIF-1a. In contrast, in the group of good responder of FLAIR (FLAIR-GR; defined as >54% of regression rate after neoBev), there were no significant differences of OS and FOXM1 expression between GR and PR. HIF-1a expression tended to be elevated in T1Gd-PR of initial tumors, T1Gd-GR of recurrent tumors, and FLAIR-PR of both initial and recurrent tumors. Conclusion: T1Gd-GR after neoBev might attribute to inhibition of FOXM1 and oxygenation. Bev might provide tumor oxygenation, leading to inhibition of stemness and M2 TAM infiltration during its effectiveness. These results suggested that Bev combined with immunotherapy for newly diagnosed GBM might provide clinical benefits including inhibition of stemness and induction of immunosupportive TME, when tumor volume assessed by T1 Gd. was significantly decreased following neoBev.